Analisa Uji Tarik dan Uji Impak Pada Komposit Sekam Padi Perlakuan NaOH dan Pengisi Plastik Polypropylene (PP) dengan Matriks Resin BQTN-157 - Isro Nurul Hadi; Sri Hastuti; Nurhadi Nurhadi; Anaya Putri Riskia; Ridwan Afandi; Roy Aries Permana Tarigan (Mechanical Engineering Department - Semarang State Polytechnic, 2023)
Utilization of rice husk is widely used as a compost medium for plants. Rice husk reinforced composite materials can be used to manufacture electric car interiors and bodies with lightweight and corrosion resistance. The purpose of this study was to analyze the mechanical properties of the results of tensile and impact testing of rice husk reinforced composites with polypropylene plastic fillers. The composite matrix uses Unsaturated Polyester BQTN-157 resin with 1-2% catalyst. Rice husk was chemically treated with 15% NaOH for 5 hours. This study used a volume fraction comparison Matrix: Rice Husk: Polypropylene (80% : 15% : 5% , 80% : 10% : 10% , and 80% : 5% : 5%). The tensile test refers to the ASTM A370 standard and the impact test refers to the ASTM E23 standard. The greatest tensile strength is found in the volume fraction of 80% : 15% : 5%, with a value of 42.13 Mpa. The modulus of elasticity decreased in the volume fraction of 80% : 10% : 10% and 80% : 5% : 5%, with a difference of 5% decrease in rice husk of 1.916,46 MPa. The decrease in the elastic modulus occurs due to the random arrangement of fiber directions. The results of the impact test obtained the highest impact value at a volume fraction of 80% : 15% : 5% , with a value of 10320.04 J/mm2.